Sarana Dan Prasarana Menuju Objek Wisata Kota Tapak Tuan Kecamatan Tapak Tuan Kabupaten Aceh Selatan - Mhd. Hirsan Hanafi; Jerry Wilson; Handoko (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2022)
This writing is a professional work of team research of Akademi Pariwisata Medan who concentrates their research in a South Aceh Regency of Tapak Tuan District. The object of the research is “FACILITIES AND INFRASTRUCTURE TOWARDS TOURISM OBJECT IN THE CITY OF TAPAK TUAN, TAPAK TUAN DISTRICT, SELATAN ACEH REGENCY”. The data of the analyses were acquired directly from website, books and directly from the real location and situation in Tapak Tuan Tourism Sites. The data acquired is the basic needs to be analyzed in order to find out the real problem of tourism sites. The purpose of analyses is to increase the visitors the Tourism Sites in Tapak Tuan by researching the real problem and situations to be analyzed and to find out the solution of the situation. The theory applied in the research is empirical theory by doing a direct observation in the area of research combined with answering question of Why and How related to the situation and condition of Tapak Tuan Tourism Area. The facilities and infrastructure needs to be seriously managed by the tourist businessman and local government. This problem must be solved immediately to increase the beneficial of tourism sites to increase the visitors as well as tourism income in Tapak Tuan Finally the writer hopes the research would be beneficial for the development of Tourism in Tapak Tuan District in South Aceh Regency Aceh Province.